All Things Possible. Issue 3 (4th May 2018) - Singer, Mark
Abstract : Noa Bar-Haim's thoughtful and impressively comprehensive paper deftly focuses on the complicated relationship between psychotherapy and psychopharmacologic treatments, and the dyadic and triadic dynamics inherent to the relationships that exist between psychotherapists, psychiatrists, and patients in the context of shared clinical work. I applaud Dr. Bar-Haim for bringing these important issues to bear. These are prodigious topics about which much can be said, and for which historically, in my estimation, not enough has been said. I am appreciative that this journal is open to including them in its scope by welcoming her thoughts and this discussion to its highly esteemed and well-respected pages. Given the vast range of topics that Dr. Bar-Haim admirably presents in her paper, and the extensive nature of what these issues encompass, this discussion addresses a selection of the many concepts she raises. It is my hope that my thoughts will serve to amplify some of hers, provide some additional and related perspectives, and mostly, have a generative effect that will promote further awareness of these issues and a continuing discussion about them within our field.